Online learning experiences of new versus continuing learners: a large-scale replication study. Issue 4 (19th May 2017) - Li, Nai; Marsh, Vicky; Rienties, Bart; Whitelock, Denise
Abstract : A vast body of research has indicated the importance of distinguishing new vs. continuing students' learning experiences in blended and online environments. Continuing learners may have developed learning and coping mechanisms for 'surviving' in such learning environments, while new learners might still need to adjust their learning approaches to the new learning context. In this large-scale replication study, we investigated whether and how the learning satisfaction experiences of 16, 670 new vs. 99, 976 continuing students were different. Using logistical regression modelling of learner satisfaction scores of 422 undergraduate blended and online modules (including 232 learner and module learning design variables), our findings indicated that new learners indeed differed subtly in their learning and teaching experiences across two consecutive academic years. The minor differences in key drivers between the 2014 and 2015 cohorts also indicate that institutions need to continuously monitor and act upon changing learning needs.